Exploring the World of Web and Grid Services: A Comprehensive Review - Kumar, Mohit (Journal of Advanced Research in Service Management, 2023)
Web and grid services have revolutionized the digital landscape, offering versatile solutions for communication, collaboration, and distributed computing. This comprehensive review explores their evolution, core concepts, advantages, and the myriad challenges they present. Web services have evolved from the early days of SOAP and XML-RPC to the RESTful architecture, embracing micro services and containerization. These services transcend platform boundaries, enabling interoperability, scalability, and loose coupling among diverse systems. While their advantages are undeniable, they pose challenges such as performance overhead, security concerns, versioning intricacies, and the need for robust monitoring and governance. In contrast, grid services delve into the complex realm of grid computing, facilitating resource management, job scheduling, data handling, and secure collaboration across distributed environments. They excel in scientific research but demand expertise to overcome challenges like resource heterogeneity and complexity. The review further explores emerging trends like server less computing, GraphQL, edge computing, quantum integration, and AI, offering glimpses into the future of web and grid services. As technology advances, these services will continue to be at the forefront, fostering innovation and addressing the ever-evolving demands of modern society across various industries. Understanding their intricacies is essential for harnessing their full potential in today's interconnected world.